Social adjustment of African children in Icelandic compulsory schools - Catherine Enyonam Sævarsson 1973- (2011)
B.A Thesis In Icelandic compulsory schools, all nationals are supposed to take teaching instructions in Icelandic. Article 16 of the National Curriculum guide, Compulsory School Act (2008) states that ―Pupils whose mother tongue is not Icelandic are entitled to instruction in Icelandic as second language.‖ The aim of this objective is to empower immigrant children to study and become active participants in Icelandic community. Does the culture of African children serve as a hindrance to adjusting socially in the school? Significantly, this study looks into the factors such as Icelandic proficiency, peer relationships, weather, food, family relationships, and school experiences. Furthermore, the study would explore theories of migration, types of migration, purpose of migration, culture and identity. Five immigrant children from Africa have participated in this study. The participants include two current and three past students from different Icelandic compulsory schools. Suggestions are made to recover the situation while I will drawing the conclusions that ´´ African children can adjust socially well in Icelandic schools, and can contribute even more positively if they are given extra attention in schools in regards to language, to breaking the cultural barrier between them and the native children. In addition, through positive motivation they will acquire the knowledge and the skills to interact meaningfully with other children as well as other people in their new environment‖. It is very essential to offer citizenship education to all students, including compulsory schools in multicultural society like Iceland.